Carved Inscriptions and Engraved Writings on The Stone Facades of Virgin Church at The Square Near Zagubica - Андрејић, Живојин Р. (Sabornost - The Theological Year-book, 2014)
This paper thoroughly deals with the study of several published writings and their new readings and explanations and then present and explain numerous other writings and engraved inscriptions from the façade of the Virgin Church near Zagubica. Based on the content of the text, some important historical individuals from the XV century are related to this church, firstly, Olivera, first wife of Djurdje Brankovic, in whose name the church was reconstructed and upgraded.